POLA ASUH SINGLE PARENT DALAM PENDIDIKAN AGAMA ISLAM ANAK DI DESA SIMANDOLAM KEC.KOTANOPAN - Pitriani, Pitriani (Jurnal Padamu Negeri, 2025)
This study aims to examine the parenting patterns adopted by single parents in the Islamic religious education of their children in Ampung Julu Village, Batang Natal Subdistrict, Mandailing Natal Regency. The research background stems from the growing phenomenon of single-parent families, which presents challenges in religious education. This is a qualitative descriptive study employing data collection methods such as observation, interviews, and documentation. The results show that single parents apply various parenting styles, including authoritarian, permissive, and democratic. The main challenges include limited time and dual responsibilities as both breadwinners and educators. Nevertheless, some single parents successfully nurture their children in the cognitive, affective, and psychomotor aspects of Islamic education through exemplary conduct, habituation, advice, supervision, and other Islamic-based methods. The study concludes that active involvement of single parents, despite limitations, still has a positive impact on the development of their children's Islamic religious education.